Analysis of Maneuvering Speed of a Passenger Ship Scalability Prototype with a Remote-Control System - Rinasa Agistya Anugrah (invotek, 2022)
They are using a passenger ship prototype as an experiment in control systems. Ship prototype control system with remote control. For this reason, research was carried out on the workings of ship prototypes, maneuver speed, long distance to the ship, and battery capacity expiration time. For this reason, research was carried out on how the prototype ship worked, the maneuvering speed, the remote reach distance to the boat, and the time the battery capacity would run out. The research was conducted using a rope, stopwatch, arc ruler, and test object. Using this tool, the results of the ship's speed when maneuvering at a predetermined angle, the maximum range of remote distance to the boat, and the length of time the battery capacity will run out. The research results tested on the remote control (RC) prototype ship showed the highest maneuvering speed at an angle of 90 degrees, which is 0.407 m/s, and the lowest rate at an angle of 180 degrees, 0.376 m/s. With this, it can be concluded that the smaller the angle of maneuver, the faster the speed of the ship to maneuver, and the greater the grade of the scheme, the slower the rate. Furthermore, the farther the remote control operating distance is from the battery speed, the faster the battery capacity will run out, and the closer the ship's rotational variation distance, the more the battery capacity will run out.